FIELD EVALUATION OF ESTRUS SYNCHRONIZATION AND PREGNANCY DETECTION USING ULTRASONOGRAPHY TO THE LOCAL AWASSI EWES FOR SHEEP OWNERS IN KANAAN DISTRICT- DIYALA PROVINCE - & Hobi, Al-Jubouri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The objective of this study was to carry out an on-farm experiment in sheep owner farms in Kanaan district for the period from 7th Feb. 2015 to 27th Mar. 2015 and to identify the unconventional methods in controlling the reproduction in sheep and increase their productivity using 45 local Awassi ewes, randomly selected from three sheep owners (15 ewes / owner). Treatment group (10 ewes/ owner) were treated with a vaginal sponges containing 20 mg fluorogestone acetate (FGA) inserted for 10 days, followed by I.M. injection of 500 IU equine chorionic gonadotropin (eCG), while 5 ewes / owner were regarded as control group without any treatment. Estrus was observed for all ewes for 5 days post withdrawal of sponges. Ewes that showed estrus were mated by rams in their flocks, thereafter, pregnancy detection was conducted at days 35-37 post- mating using transabdominal ultrasonography. A questionnaire involved 20 sheep owners and a demonstrative field day was conducted for owners contributed in the experiment, and others from the region of study to explain the importance and results of the experiment. The results showed the appearance of estrus in all ewes 100% within three days after the withdrawal of sponges. Pregnancy rate of  85.71% at days 35-37 of mating. The questionnaire showed there is an urgent need of knowledge for owners to find out the importance of controlling the reproductive cycle in sheep using vaginal sponges. Also, there were a correlation between the need of knowledge for sheep owners with (educational level for most of them, herd sizes, income from breeding, training courses and other activities in the fields of breeding and reproduction of sheep). In conclusion, the technology of estrus synchronization has an important role to improve reproductive performance of sheep and pregnancy could be detected through transabdominal ultrasonography at 35-37 days with high accuracy as well as there is great desire for the most owner to conduct estrus synchronization technique and to take care their birth of herds simultaneously.